Arresting tumor cell proliferation and inhibition of AKT pathway via the use of multikinase inhibitor sorafenib forthe treatment of glioblastoma - Raju, Md. Ismail (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2022.